2D Model and 3D Reconstitution of Sintered Metal Fibers by Surface Diffusion. Issue 6 (June 2017) - Dongdong, Chen; Zhoushun, Zheng; Jianzhong, Wang; Huiping, Tang
Abstract: According to the sections of sintered junction of two metal fibers, which are oval-oval geometry structure in different directions, an oval-oval model was developed based on the traditional surface diffusion mathematical model. This model was numerically solved by a level set method to achieve the 2D simulations of two sintered metal fibers. Moreover, the 3D reconstitution method was proposed to depict the complex 3D geometrical structure of sintered junction. The 2D simulations and 3D reconstitution results of two metal fibers with the fiber angle 30° well agree with the experimental ones, which imply that the 2D model and 3D reconstitution method are correct. In addition, the numerical simulation results show that the growth rate of sintered neck along the directions taken from the bisector of obtuse angle to the bisector of acute angle is increased.